24. A MODEL OF FACTORS CONTRIBUTING TO PERSONAL EXPOSURE TO PM2.5 IN HO CHI MINH CITY (Vietnam Journal of Community Medicine, 2024)
Objectives: To build a model of factors contributing to personal exposure to PM2.5. Included factors were background characteristics, location, transportation, activities, ventilation status, air quality.Methods: A longitudinal follow-up study conducted on 36 volunteers in Ho Chi Minh City. They wore PM2.5 measuring devices for 2 consecutive days and completed corresponding Time-activity diaries (TAD).Results: The median PM2.5 concentration level was 14 µg/m3. The Bayesian Model Average (BMA) determined the contribution of factors including 8 variables: Age, weekend, humidity, rain, outdoor location, smell of smoke, smell of dust, eating in a restaurant had the lowest BIC of -436.4, explaining 29.6% of the variation in personal PM2.5 exposured. Smoke-smelling environments contributed the highest at 17%. The following factors were the age, rain, outdoor location, and weekends which contributed about 2-4%. The factors of humidity, dusty environment and eating in a cafeteria/restaurant contribute less than 1%.Conclusion: It is necessary to control smoke from restaurants and eateries to reduce personal exposure to PM2.5 in Ho Chi Minh City.
Keywords: PM2.5, personal exposure, contributed factors, predicted model